2014
DOI: 10.1021/la500384r
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adsorption Kinetics of Asphaltenes at the Oil–Water Interface: A Random Sequential Adsorption Perspective

Abstract: Previous studies indicated that asphaltenes adsorbed as monomers on oil-water interfaces and the early stage kinetics of the process was controlled by diffusion and hence dependent on oil viscosity. By measuring interfacial tension (IFT) as a function of surface coverage during droplet expansions in pendant drop experiments, it was also concluded that the IFT data could be interpreted with a Langmuir equation of state (EoS), which was independent of oil viscosity, time of adsorption, and bulk asphaltenes conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 54 publications
18
111
0
Order By: Relevance
“…In addition, the perpendicular orientation of PAC molecules observed here can be partly attributed to the oxygen functional groups, such as ketone and ester, present in the chemical structures. For PAC molecules without oxygen moieties, their polyaromatic core may prefer parallel to the interface, as reported by Banerjee and co-workers [15][16][17][18]. Indeed, it has been suggested by Mullins and co-workers 19,20 that the presence of oxygen moiety can alter the preferred orientations of PAC molecules from being parallel to being perpendicular.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, the perpendicular orientation of PAC molecules observed here can be partly attributed to the oxygen functional groups, such as ketone and ester, present in the chemical structures. For PAC molecules without oxygen moieties, their polyaromatic core may prefer parallel to the interface, as reported by Banerjee and co-workers [15][16][17][18]. Indeed, it has been suggested by Mullins and co-workers 19,20 that the presence of oxygen moiety can alter the preferred orientations of PAC molecules from being parallel to being perpendicular.…”
mentioning
confidence: 74%
“…That is, in ݊-heptane, PAC molecules migrate to the interface and their adsorption tends to be irreversible, 17 while in toluene, they are more prone to being solvated in the bulk toluene phase, and completely detachment, i.e. reversible adsorption, is observed.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…On the other hand, other studies 30,31 showed that there is no reorganization or cross-linking at the interface and that asphaltenes are adsorbed as monomers instead of nanoaggregates. This was concluded after fitting adsorption data to an equation of state (Langmuir EoS) which yielded an adsorbed amount that would only be possible if a flat-on adsorption of asphaltene monomers occurred.…”
Section: Introductionmentioning
confidence: 93%
“…The RSA particle adsorption simulations (governing logic can be found in [10,11]) indicate that the additional of 65 nm diameter particles in the second step is due to their adsorption in the interstices of the bigger particles adsorbed in the first step and the smaller particles introduced in step 2 do not cause the bigger particles adsorbed in the first step to move laterally on the surface. This was further confirmed from the coinciding pair co-relation function plots for the 90 nm diameter particles (Fig.…”
Section: Resultsmentioning
confidence: 99%